Growth Of Male Turkey at Different Energy Levels - Awal, Awal; Sarjuni, Sri; Tantu, Rizal Y (AgriSains, 2020)
Turkey is a type of poultry from the order Galliformes, the genus Meleaagriss which is starting to get public attention for cultivation. The cultivation of turkey in Indonesia is still lacking, most of the breeders prefer other types of poultry. Turkey is a type of poultry that has the potential to be developed as a meat animal, because it has a large body size and is able to utilize feed ingredients in the form of grains and forage. This study aims to determine the growth of male turkeys aged 19-25 weeks at different energy levels. The research was carried out in the experimental cage of the Faculty of Animal Husbandry and Fisheries in South Sibalaya Village, Tanambulava District, Sigi Regency, on June 24 - July 29 2018. The study used a completely randomized design (CRD) with 3 treatments and 5 replications. The treatments are R1 = Rations with Metabolic Energy of 2800 Kcal/Kg, R2 = Rations with Metabolic Energy of 2900 Kcal/Kg, R3 = Rations with Metabolic Energy of 3000 Kcal/kg. The variables observed were rations consumption, body weight gain and rations conversion. The results showed that the treatment had a significant effect (P <0.05) on rations consumption, had no significant effect (P> 0.05) to increase of body weight and rations conversion. Using energy levels of 3000 Kcal/Kg gives a positive result on rations consumption for male turkeys aged 19-25 weeks.